Rheumatology and therapy.
Rheumatology and Therapy is an international, open access, peer-reviewed, rapid publication journal (peer review in 2 weeks, published 3-4 weeks from acceptance). The journal is dedicated to the publication of high-quality preclinical, clinical (all phases), observational, real-world, and health outcomes research around the discovery, development, and use of rheumatologic therapies. Studies relating to diagnosis, pharmacoeconomics, public health, quality of life, and patient care, management, and education are also encouraged.